The philosophy source 100 classic masterworks on CD-ROM [electronic resource] - Kolak, Daniel (Wadsworth, 2000)
Provides access to classic philosophical text from ancient to modern times, including works by Aristotle, Hume, Kant, Marx, Nietzsche, and Rousseau.